Revision of the evacanthine leafhoppers (Hemiptera: Cicadellidae: Evacanthinae) of the Indian subcontinent - Viraktamath, C.a.; Webb, M.d. (Zootaxa, 2018)
The leafhoppers of the tribe Evacanthini of the Indian subcontinent (Pakistan, India, Nepal, Bhutan, Bangladesh, Myanmar and Sri Lanka) are reviewed. The genus Apphia Distant 1918, is reinstated as a valid genus from synonymy with Onukia Matsumura stat. rev. and redefined based on the male genitalia characters. The genus Angustuma Xing & Li 2013, (new name for Angustella Li 1986, not Waagen 1907) is considered a junior synonym of Apphia. The genera Carinata Li & Wang, Concavocorona Wang & Zhang, Risefronta Li & Wang, Shortcrowna Li & Li, Striatanus Li & Wang and Taperus Li and Wang along with Bundera bambusana Yang, Chen & Li, Carinata midfasciana Wang & Li, Onukia albiclypeus Li & Wang, O. flavocapitata Li & Wang and Risefronta albicincta Li & Wang are here recorded for the first time from the Sub-Himalayan region of the Indian subcontinent. Keys to genera and included species are given. The new taxa recognized are Apphia flava sp. nov. (India: Meghalaya), Bundera acutivertex sp. nov. (India: Mizoram), Concavocorana kambaiti sp. nov. (Myanmar; Kambaiti), Evacanthus albipennis sp. nov. (Nepal), E. convolutus sp. nov. (India: Himachal Pradesh), E. distinctus sp. nov. (India: Himachal Pradesh), E. manaliensis sp. nov. (India: Himachal Pradesh), E. yeshwanthi sp. nov. (India: Meghalya), Onukia echina sp. nov. (India: Manipur), Onukindia gen. nov. (type species : Platyretus connexus Distant), Onukindia aruna sp. nov. (India: Arunachal Pradesh), O. compressa sp. nov. (India: Arunachal Pradesh, West Bengal), Shortcrowna rubrostriata sp. nov. (Myanmar: Kambaiti), Striatanus delta sp. nov. (India: West Bengal; Mizoram) and Taperus indicus sp. nov. (India: Arunachal Pradesh). The following new combinations (genera of original combination in parenthesis): Apphia albida Li & Li) comb. nov., A. albonotata (Yang & Zhang) comb. nov., A. basinigra (Wang & Zhang) comb. nov., A. flavimacula (Wang & Zhang) comb. nov., A. flavinigra (Wang & Zhang) comb. nov., A. jinghongensis (LI & Li) comb. nov., A. leucostriata (Li & Wang) comb. nov., A. longipyga (Li & Wang) comb. nov., A. nigricarina (Li) comb. nov., A. nigricauda (Cheng, Yang & Li) comb. nov., A. nigrimargina (Li & Li) comb. nov., A. nigrinota (Yang & Zhang) comb. nov., A. pallida (Cai & He) comb. nov., A. panxianensis (Li & Li) comb. nov., A. rudorsuma (Xing & Li) comb. nov. and A. rufipenna (Li & Wang) comb. nov. (all from Angustuma), Apphia assamensis (Ramakrishnan) comb. nov. (Dussana), Apphia himalayana (Distant) comb. nov. (Platyretus) and Onukindia connexa (Distant) comb. nov. (Platyretus) are made. Evacanthus repexus Distant and Vangama steneosaura Distant appear to be species complexes and need to be further investigated. Lectotypes are designated for: Apphia burmanica Distant, Apphia himalayana (Distant), Bundera venata Distant, Cunedda phaeops Distant, Evacanthus bellus (Distant), Evacanthus militaris (Distant), Evacanthus repexus Distant, Mainda praeculta Distant, Onukindia connexa (Distant) and Vangama steneosaura Distant.